Direct and indirect community affiliation as a tool to mitigate marine waste in Semporna, Sabah a rural tourism setting - Prabhakaran, Sudesh; Nair, Vikneswaran; Ramachandran, Sridar (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Semporna is a rural district, which is situated in the east cost of Sabah, Malaysia. Semporna is becoming popular due to its marine tourism activities. This paper presents a discussion of how the communities in Semporna can be distinctively categorised as direct and indirect communities. This distinction can be used further as a mechanism to understand the respondents for effectively mitigating marine waste. The study also reviews the methodological characteristics of community participation’s theory and the extension of it. The paper is constructed based on the understanding and criticism of many authors work from previous studies. Finally, this paper provides a theoretical understanding for the readers to look at the community in a different perspective in the context of managing the environment responsibly in a rural tourism destination.